Transformation of the state planning system — from state programs to national projects: the experience of Russia - Roslyakova, N.; Vechkinzova, E. (KU Publ., 2021)
Object: Today, almost all countries of the world use a program-target approach to the development of the country's economy. Regional, industrial and government programs, national projects have become an integral part of the country's socio-economic activity, a tool for solving topical problems and achieving specific goals in various sectors of the economy. The transition from the format of state programs to national projects means changing the approach to solving topical issues. National projects are a direct state response to current system requests from society. The new state management format also requires the revision of the mechanism of selecting monitoring and updating of development projects. The purpose of this article is to study the practice of managing current national projects in Russia as a development tool. Methods: During the research, the methods of comparative analysis of the practice of selection and evaluation of the effectiveness of national projects in the regions of Russia; analysis of the expert opinions on the experience of monitoring and implementing existing national projects of Russia have been applied. Results: In the result of research the mechanisms of selection, monitoring and re-enabling projects into the system of national projects of Russia; the problems of coordination and linking the mutual interests of the beneficiarys and administrators of projects and ways to develop the mechanisms of coordination of interest have been identified. Conclusions: Summarizing the studied experience of Russia in the transition from state programs to national projects, a new approach to the mechanism of dynamic monitoring and update of projects can be highlighted, when projects with low implementation efficiency are excluded from the composition of national projects. In their place, from the projects that have passed the examination and have a high assessment of the quality of their development come from “basement of projects”. Despite this positive practice in the management of national projects, the following problem areas can be identified: systemic management problems, poor planning quality in the formation of a system of project indicators, motivational problems.
Мемлекеттік жоспарлау жүйесін трансформациялау — мемлекеттік бағдарламалардан ұлттық жобаларға дейін: Ресей тәжірибесі
Трансформация системы государственного планирования — от государственных программ к национальным проектам: опыт России
Keywords: program-target management; government programs; project approach; national projects; development tools